Evaluasi Standar Nasional Pendidikan Tinggi Studi Kasus STKIP Nasional - Sepniwita, Sepniwita (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Nasional, 2021)
ABSTRACT The purpose of this study was to analyze in depth the implementation of SN DIKTI in the aspects of education and learning. The analysis is carried out through program evaluation starting from Context, Input, Process, Product, and Outcome. The type of research is Evaluation Research which is carried out in the National STKIP environment. The results of the research are (1) Study Program requires lecturers to prepare teaching materials based on KKNI; (2) the development of science and technology (Science and Technology) based on the results of research and service and provide enlightenment in fostering faith and piety (Imtaq); (3) the implementation of Reward and Punishman for lecturers implementing or violating any SOP that applies to study programs; (4) the study program implements a monitoring mechanism for student attendance, the presence of lecturers, and the suitability of the lecture material taught with the syllabus and RPS for each meeting based on the SOP for the lecture monitoring and evaluation mechanism and the results are followed up. It can be concluded that this alternative policy can be trusted and can be used as a guide in the development of National Education Standards at the National STKIP.